2016
DOI: 10.1080/09540121.2016.1191611
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a physiotherapy-led group rehabilitation intervention for adults living with HIV: referrals, adherence and outcomes

Abstract: HIV is characterised by episodes of disability. We report a novel, hospital outpatient rehabilitation intervention, combining physiotherapy-led group exercise and education for people living with HIV (PLWH). This observational study evaluated routine delivery of the 10-week intervention in terms of referral patterns, rehabilitation goals, intervention adherence and change in patient outcomes. Measurements at baseline & 10 weeks included locomotor performance (6 minute walk test; 6MWT), flexibility, upper and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 53 publications
0
37
0
3
Order By: Relevance
“…Despite the medical advances in HIV management with antiretroviral therapy, older PLWH appear to experience age-associated comorbidities at a higher rate and at a younger age than the general population 2 35. The physical barriers attributed by our participants to HIV and medication, generalised fatigue, and chronic pain are consistently identified as barriers to exercise among PLWH 28 31–33 36. To engage older PLWH, exercise interventions must acknowledge and address these physical barriers.…”
Section: Discussionmentioning
confidence: 94%
“…Despite the medical advances in HIV management with antiretroviral therapy, older PLWH appear to experience age-associated comorbidities at a higher rate and at a younger age than the general population 2 35. The physical barriers attributed by our participants to HIV and medication, generalised fatigue, and chronic pain are consistently identified as barriers to exercise among PLWH 28 31–33 36. To engage older PLWH, exercise interventions must acknowledge and address these physical barriers.…”
Section: Discussionmentioning
confidence: 94%
“…The HIV CBE intervention is a 24-week exercise programme at the Central Toronto YMCA. The intervention is derived from high-quality research evidence on the effectiveness of exercise with PLWH, recommendations from the American College of Sports Medicine, 21 qualitative consultation with community (PLWH and fitness instructors), 36 pilot work 37 and existing HIV rehabilitation services in the UK, 46 collectively adapted for the Canadian context. We chose a 6-month CBE duration because it aligns with transtheoretical model evidence on the stages of behaviour change whereby the ‘action’ of practicing a new behaviour (exercise) lasts up to 24 weeks followed by the ‘maintenance’ stage during which commitment to sustaining the new behaviour (self-monitored exercise) is solidified.…”
Section: Methodsmentioning
confidence: 99%
“…Participants will also attend monthly group educational sessions co-led by a health or fitness professional and/or PLWH focused on topics related to self-management and healthy living with HIV. 46 A variety of topics will be covered in six sessions, including stress management and relaxation, pain management, nutrition, fatigue management, smoking cessation, goal setting, confidence to self-manage, community services and supports and rehabilitation in the context of HIV. 46 Throughout the intervention, participants will be asked to complete a weekly online exercise log to document their physical activity.…”
Section: Methodsmentioning
confidence: 99%
“…They found that this exercise schedule was effective in providing improved cardiovascular fitness and higher endurance performance. Similarly, Brown et al [42] assessed the efficacy of a physiotherapy-led. Group-rehabilitation intervention program involving physical exercise to implement function in HIV patients with regard to referrals, adherence and outcomes; they obtained improvements in the six-minute walk test, strength in triceps and biceps, lattisimus dorsi, shoulder-press, chest-press and leg-press, and the physical, emotional and functional subscales, with higher levels of valid expectancies.…”
Section: Editorialmentioning
confidence: 99%